2004
DOI: 10.1038/ni1039
|View full text |Cite
|
Sign up to set email alerts
|

ERM proteins regulate cytoskeleton relaxation promoting T cell–APC conjugation

Abstract: During activation, T cells associate with antigen-presenting cells, a dynamic process that involves the formation of a broad area of intimate membrane contact known as the immunological synapse. The molecular intermediates that link initial antigen recognition to the cytoskeletal changes involved in this phenomenon have not yet been defined. Here we demonstrate that ezrin-radixin-moesin proteins are rapidly inactivated after antigen recognition through a Vav1-Rac1 pathway. The resulting disanchoring of the cor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

16
230
1
4

Year Published

2005
2005
2016
2016

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 250 publications
(253 citation statements)
references
References 50 publications
16
230
1
4
Order By: Relevance
“…Ezrin is present in a phosphorylated form in cells before stimulation through Fas, antigen receptors or chemokine receptors, and is dephosphorylated after these stimulations (Kondo et al, 1997;Delon et al, 2001;Brown et al, 2003;Faure et al, 2004;Gupta et al, 2006;Hao et al, 2009). Our observation that ezrin was dephosphorylated after FasL stimulation in T cells (Figure 1c) is in accordance with those reports.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…Ezrin is present in a phosphorylated form in cells before stimulation through Fas, antigen receptors or chemokine receptors, and is dephosphorylated after these stimulations (Kondo et al, 1997;Delon et al, 2001;Brown et al, 2003;Faure et al, 2004;Gupta et al, 2006;Hao et al, 2009). Our observation that ezrin was dephosphorylated after FasL stimulation in T cells (Figure 1c) is in accordance with those reports.…”
Section: Discussionsupporting
confidence: 92%
“…How ERM participates in several membrane-associated events in lymphocytes remains unclear. For example, three different roles have been reported for the involvement of ezrin-moesin in immunological synapse (IS) formation: ERM was found to be essential for the assembly of IS and the recruitment of ZAP70 in one group of studies (Roumier et al, 2001;Ilani et al, 2007); ezrin was reported to be completely dispensable for IS formation in another study (Shaffer et al, 2009); and in yet a third proposal, ezrin was also declared to negatively regulate IS formation (Faure et al, 2004). Similarly, opposite effects of ERM have been documented for T-lymphocyte movement; T-cell migration could be enhanced by either ERM phosphorylation (Li et al, 2007) or ERM dephosphorylation (Brown et al, 2003).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…No proliferation occurred in a pure CD4 + T cell population stimulated with only PHA, which emphasizes the importance of a focal stimulation and the formation of an IS for an efficient immune response [28,29]. PHA is known to act as a cross-linker molecule that binds to glycoproteins all over the cell surface.…”
Section: Discussionmentioning
confidence: 96%
“…This is consistent with previous findings that ERM is essential for Rac family protein-induced cytoskeletal configuration and Rac1 can regulate ERM phosphorylation. 17,34,[53][54][55] In searching for the intermediate signaling molecule linking Rac1 activation and ERM phosphorylation, we found that Pak1, a serine/threonine kinase is a downstream target of Rac1 activation, accounts for ERM phosphorylation. It has been reported that Pak1 is involved in the phosphorylation activation of merlin, a highly homologous protein to ERM family members.…”
Section: Discussionmentioning
confidence: 99%